2016
DOI: 10.1016/j.jecp.2015.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Three-year-olds’ rapid facial electromyographic responses to emotional facial expressions and body postures

Abstract: Rapid facial reactions (RFRs) to observed emotional expressions are proposed to be involved in a wide array of socioemotional skills, from empathy to social communication. Two of the most persuasive theoretical accounts propose RFRs to rely either on motor resonance mechanisms or on more complex mechanisms involving affective processes. Previous studies demonstrated that presentation of facial and bodily expressions can generate rapid changes in adult and school-age children's muscle activity. However, to date… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
48
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(58 citation statements)
references
References 96 publications
6
48
3
Order By: Relevance
“…Adults show facial EMG reactions to both unimodal facial expressions (visual only) [4][5][6]41,42] and emotional vocalization (auditory only) [6]. A recent study showed that even three-year-old children show the mimicking responses to unimodal facial expressions [27]. In contrast to those previous findings in adults or children, our results revealed that four-to five-month-old infants do not show mimicking responses towards emotional faces and vocalization.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Adults show facial EMG reactions to both unimodal facial expressions (visual only) [4][5][6]41,42] and emotional vocalization (auditory only) [6]. A recent study showed that even three-year-old children show the mimicking responses to unimodal facial expressions [27]. In contrast to those previous findings in adults or children, our results revealed that four-to five-month-old infants do not show mimicking responses towards emotional faces and vocalization.…”
Section: Discussioncontrasting
confidence: 99%
“…The results showed increased activations of the corrugator supercilii in response to audiovisual crying, and the zygomaticus major in response to audiovisual laughing, between 500 and 1000 ms after the stimulus onset. Consistent with the findings of previous studies with adults [4,5] and children [27,[35][36][37], infants' muscles activity in response to audiovisual emotional displays emerged and peaked between rspb.royalsocietypublishing.org Proc. R. Soc.…”
Section: Discussionsupporting
confidence: 89%
“…In accord with the idea that angry faces represent a source of potential threat, electrophysiological data collected from a wide range of age groups show that observing angry faces elicits reactions of fear (e.g., Beall, Moody, McIntosh, Hepburn, & Reed, ; Geangu, Quadrelli, Conte, Croci, & Turati, ; Moody, McIntosh, Mann, & Weisser, ). For example, Geangu and colleagues () reported that observing pictures of angry facial expressions in children triggered an increased electromyographic activation of the frontalis muscle, which is typically involved in expressing fear. Behavioral and neuroimaging studies have also shown that neural sensitivity to facial expressions of anger emerges early in development (Ravicz et al, ; Vaish et al, ).…”
Section: Introductionmentioning
confidence: 83%
“…In adults, heightened activation of the amygdala has traditionally been associated with increased reactivity to fearful expressions (e.g., Davis & Whalen, 2001), but there is also evidence for its responsiveness to angry faces (e.g., Whalen et al, 2001). In accord with the idea that angry faces represent a source of potential threat, electrophysiological data collected from a wide range of age groups show that observing angry faces elicits reactions of fear (e.g., Beall, Moody, McIntosh, Hepburn, & Reed, 2008;Geangu, Quadrelli, Conte, Croci, & Turati, 2016;Moody, McIntosh, Mann, & Weisser, 2007). For example, Geangu and colleagues (2016) reported that observing pictures of angry facial expressions in children triggered an increased electromyographic activation of the frontalis muscle, which is typically involved in expressing fear.…”
Section: Introductionmentioning
confidence: 99%
“…The F muscle was measured as a control muscle, to examine the possibility that infants responded with fear rather than with anger to angry kinematics. Several studies (Beall, Moody, McIntosh, Hepburn, & Reed, ; Geangu, Quadrelli, Conte, Croci, & Turati, ) showed that children sometimes respond to angry facial expressions with fearful facial reactions (increased activation of frontalis muscle) rather than with anger (increased activation of corrugator supercilii muscle). These results suggest that children evaluated an angry face as a potential threat for them (Geangu et al, ).…”
Section: Introductionmentioning
confidence: 99%